Evaluation of the cross-plane thermal conductivity of double-layer materials. (1st February 2017) - Kim, Jong-Gu; Bae, Dong-Hyun; Hahn, Byung-Dong; Cho, Young-Rae
Abstract: Double-layer cladding materials were fabricated by roll bonding using stainless steel (STS439) and aluminum (Al1050) sheets to investigate the thermal conduction of multi-layer composites. The measured thermal conductivities were compared to values calculated from cross-plane models that are widely used for resistor connections in electrical circuits. The measured thermal conductivity was 88.3 W/m·K for the sample containing 76 vol% of Al1050. Unexpectedly, the measured cross-plane thermal conductivities were always higher than the values calculated from the series model. The high cross-plane thermal conductivities were attributed to the contribution of phonons to thermal transfer. A deviation index of the thermal conductivity, Fm(S), is proposed, which effectively describes the cross-plane thermal conductivity characteristics of double-layer materials.